Elimination of lymphatic filariasis in South East Asia - Specht, Sabine (BMJ, 2019)
Expanding treatment options alongside ensuring high coverage of mass drug administration can accelerate progress in elimination of lymphatic filariasis, say Sabine Specht and colleagues